2014
DOI: 10.1111/gfl.12074
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Pleistocene glacial loading on abnormal pore‐water pressure in the eastern Michigan Basin

Abstract: The hydromechanical effects of Pleistocene glacial loading on the Michigan Basin are assessed using numerical analysis based on coupled stress and pore-water pressure. The two-dimensional model domain included the Basin cross section and extended 10 km into the Precambrian. In the analysis, we considered the effects of the number of glacial loading cycles, the presence and connectedness of a deep Cambrian aquifer, the direction of glacial advance, the effect of a wet versus dry glacier/soil interface, topograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 37 publications
(88 reference statements)
5
32
0
Order By: Relevance
“…The Cambrian units have a very high horizontal hydraulic conductivity of 3.0 × 10 −6 m/s [5,61] which can dissipate transient hydraulic perturbations efficiently. Similar findings were reported by Khader and Novakowski [30] using a twodimensional model. The analyses of Sykes et al [37] included one simulation that allowed the Cambrian aquifer to drain and an underpressure in the middle Ordovician formed by the end of one glacial cycle; however, additional glacial cycles were not simulated.…”
Section: Simulation Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The Cambrian units have a very high horizontal hydraulic conductivity of 3.0 × 10 −6 m/s [5,61] which can dissipate transient hydraulic perturbations efficiently. Similar findings were reported by Khader and Novakowski [30] using a twodimensional model. The analyses of Sykes et al [37] included one simulation that allowed the Cambrian aquifer to drain and an underpressure in the middle Ordovician formed by the end of one glacial cycle; however, additional glacial cycles were not simulated.…”
Section: Simulation Results and Discussionsupporting
confidence: 91%
“…Following the work of Sykes et al [37], the twodimensional model studies of Nasir et al [29] and Khader and Novakowski [30] illustrated that formation underpressures could be partially attributed to the removal of glacial ice loads. The authors suggested that discrepancies between the model predicted results and observed underpressures could be the result of factors not evaluated, such as the presence of a gas phase, osmotic pressure, and/or erosion.…”
Section: Prior Analyses Of Bruce Site Underpressuresmentioning
confidence: 96%
See 1 more Smart Citation
“…[] obtained underpressures in simulations when upper boundary head, representing a surficial aquifer, did not increase during episodes of ice cover. Khader and Novakowski [] also obtained underpressures when head in the Cambrian aquifer rose only minimally during glaciation. To emulate these results we considered variants of the base case in which first G 2 (middle boundary) and then G 3 (bottom boundary) was set at 0.1, so that heads increased by only about one tenth of ice height during glaciation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, both Nasir et al . [] and Khader and Novakowski [] obtained underpressures more or less like those observed by simulating hydrologic changes and mechanical loading in two‐dimensional domains. The different outcomes may reflect different representations of conditions during glacial cycles or subsurface properties, suggesting that the response of the groundwater system can depend strongly on them.…”
Section: Introductionmentioning
confidence: 93%